НАЙПРОСТІШІ МОДЕЛІ РОСТУ МІКРОВОДОРОСТЕЙ. 9. ТЕМНОВІ ПРОЦЕСИ - Тренкеншу, Р. П.; Авсіян, Г. Л.; Новікова, Т. М. (Marine Ecological Journal, 2023)
Generalised quantitative model of kinetics and dynamics of dark processes in microalgae cells is constructed basing on the known data about dark respiration and experimental data about dark biomass loss. The model allows to describe dynamics of change of biochemical components: carbohydrates, protein and lipids in the dark conditions in microalgae culture, dynamics of cells respiration rate in the dark. When average values of specific respiration rate of phytoplankton are used the model describes the experimental results obtained in experiments with microalgae cultures with good accuracy. Upper and lower bounds of microalgae cultures respiration rates are derived which almost completely coincide with experimental estimations of these values measured by various authors.